Integrasi Presisi Profil Molekuler Radiologis dan Klinis dalam Diagnosis dan Penatalaksanaan Congenital Megacalyces - Rian Hendriyana Dwi Imanta; Fairuz Rafi Fadlurrahman; Maya Ganda Ratna; Giska Tri Putri (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Congenital Megacalyces is a rare anomaly of the renal pelvis-calyceal system characterized by non-obstructive calyx dilatation due to renal medulla hypoplasia. This condition is often misinterpreted as hydronephrosis, leading to unnecessary surgical interventions. Advances in genomic technology and precision imaging have opened up opportunities to understand the molecular basis and anatomical structure of this anomaly more deeply. A literature review was conducted through PubMed, ScienceDirect, and Google Scholar, covering publications that discuss the relationship between genomics, imaging, and clinical management of congenital kidney abnormalities. The integration of Next Generation Sequencing (NGS), 3D MRI reconstruction imaging, and AI-based radiomics analysis has proven to enhance diagnostic accuracy, differentiate between obstructive and non-obstructive abnormalities, and assist in determining appropriate conservative therapies. Case studies demonstrate the association between SETBP1 mutations and the development of bilateral megacalyces, as well as the effectiveness of long-term monitoring based on multimodal data. The integration of genetic, imaging, and clinical data is a strategic step toward precision medicine in the management of Congenital Megacalyces. This approach improves diagnostic accuracy, reduces unnecessary invasive interventions, and supports individualized therapy based on genetic and anatomical risk factors.